Tantangan dan Keuntungan Belajar Bahasa Jerman bagi Penutur Bahasa Indonesia - Ladies, Danis; Angel, Natasya; Damanik, Ezra; Azizah, Nurul (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to analyze the challenges and advantages of learning German for Indonesian speakers. Some of the main challenges include differences in grammatical structure, case system (Nominative, Accusative, Dative, and Genitive), complex verb conjugation, and pronunciation that differs from Indonesian. On the other hand, there are several benefits to learning German, such as wide educational opportunities in Germany, better career prospects, and access to rich German culture and literature. With effective learning methods, such as the use of technology, active speaking practice, and understanding language patterns, challenges in learning German can be minimized. The results of the study show significant challenges related to differences in phonological systems, grammar, and vocabulary.